Major Arthur Glyn Leonard (1909). Islam, Her Moral and Spiritual Value: A Rational and Psychological Study. London: Luzac. 160 Pages. - Çaksen, Hüseyin (Journal of Al-Tamaddun, 2023)
Major Arthur Glyn Leonard (1856-1939) was a soldier, ethnographer, and Rhodesian pioneer. However, he was far from typical in racial outlook of his fellow Rhodesian pioneers underlined in his book, entitled “Islam. Her Moral and Spiritual Value. A Rational and Psychological Study.” A flattering foreword was noted to the book by Syed Ameer Ali (1849-1928), order of the star of India, an Indian/British Indian jurist, a prominent political leader, and author of a number of influential books on Muslim history and the modern development of Islam.